Putting Make It Charlotte on the map : innovating use for street-level urban space - Banerjee, Anandi; Berka, Gregory Charles; Lee, Jae Hwan (London : Society for Case Research, 2021)
Lindsey Braciale and Jason Wolf wanted to determine the best use of a vacant 3,200-square-foot street-level commercial space in Charlotte's Uptown district. The nonprofit formed by Braciale in 2015, Make It Charlotte, had the goal of increasing opportunities for upward economic mobility for members of the Charlotte community. In a 2014 study by Harvard/UC Berkeley, Charlotte was ranked the lowest in large metropolitan areas for upward economic mobility. The commercial space under consideration was close to many highly frequented and populated Uptown locations. In addition, the space was connected to another property owned by Wolf. Braciale and Wolf desired to be creative with the space while supporting Make It Charlotte's goals. A proposal for space use was due next week to the board of Make It Charlotte, as the space had sat vacant for over a year. What was the answer?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nonprofit organizations -- North Carolina -- Charlotte -- Case studies; Public spaces -- Management -- Case studies